Гидроэлектростанция - Федорчук Ю. М. Юрий Митрофанович; Белая М. А. Марина Анатольевна; Вашкевич А. Г. Александр Георгевич; Гришагин В. М. Виктор Михайлович; Зыков В. М. Владимир Михайлович; Коркин С. Д. Сергей Данилович; Лукутин Б. В. Борис Владимирович; Недавний О. И. Олег Иванович; Романенко С. В. Сергей Владимирович; Ушаков В. Я. Василий Яковлевич; Облупин Г. А. Геннадий Анатольевич
опубл. 10.11.10